Abnormalities of plasma cytokines and spleen in senile APP/PS1/Tau transgenic mouse model - Yang, Seung-Hoon; Kim, Jiyoon; Lee, Michael Jisoo; Kim, YoungSoo (NATURE PUBLISHING GROUP, 2015)
The blood-based diagnosis has a potential to provide an alternative approach for easy diagnosis of Alzheimer's disease (AD) with less invasiveness and low-cost. However, present blood-based AD diagnosis mainly focuses on measuring the plasma A beta level because no other biomarkers are found to possess evident transport mechanisms to pass the blood-brain barrier. In order to avoid diagnosing non-demented individuals with A beta abnormality, finding additional biomarkers to supplement plasma A beta is essential. In this study, we introduce potential neurodegenerative biomarkers for blood-based diagnosis. We observed severe splenomegaly and structural destruction in the spleen with significantly decreased B lymphocytes in senile APP(swe), PS1(M146V) and Tau(P301L) transgenic mice. We also found that inflammatory cytokines associated with splenic dysfunction were altered in the plasma of these mice. These findings suggest potential involvement of the splenic dysfunction in AD and the importance of biomarker level alterations in the plasma as putative diagnostic targets for AD.
Keywords: ALZHEIMERS-DISEASE; NEUROPSYCHIATRIC SYMPTOMS; COGNITIVE IMPAIRMENT; A-BETA; TAU; DIAGNOSIS; MILD; PET; NEUROPATHOLOGY; BIOMARKERS